Clinical and diagnostic insights into brucellar arthritis: a single-center retrospective cohort study - Feng, Qiangsheng; Song, Yuejuan; Xing, Yuan; Ha, Xiaoqin (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThis study evaluates the diagnostic value of etiological and serological testing in distinguishing brucellosis arthropathy from other inflammatory joint diseases.MethodsA retrospective analysis was conducted on 68 cases of brucellosis arthropathy diagnosed between 2012 and 2024, alongside 60 non-infected controls. Bacterial cultures were performed using blood, joint fluid-blood bottle culture, and joint tissue samples, with microbial identification via VITEK Compact-II or MALDI-TOF MS. Clinical features, serological results (Standard Agglutination Test [SAT] and Rose Bengal Test [RBT]), and imaging findings were analyzed. The diagnostic performance of biomarkers was assessed using receiver operating characteristic (ROC) curves.ResultsAmong the 68 cases, 22 (32.4%) were confirmed by bacterial culture, with Brucella melitensis identified as the causative agent. Joint fluid-blood bottle culture was the most effective method (62.2%), with a mean detection time of 74.8 ± 17.9 hours (range: 41–110 hours) in aerobic bottles. Blood culture and joint tissue culture yielded positive results in 40.9% and 4.5% of cases, respectively. Brucellosis arthropathy accounted for 7.5% of total brucellosis cases, predominantly affecting males (67.6%) with a median age of 43.1 ± 13.2 years. Brucellosis arthropathy infection median time were 90[30,343] days. The knee joint was the most commonly affected site (64.7%), followed by the hip (20.6%) and sacroiliac joints (10.3%). Imaging revealed septic arthritis (20.7%), joint effusion (31.0%), bone destruction (12.0%), degenerative changes (10.3%), and prosthetic joint infection (6.9%). The sensitivity for Brucella culture, SAT, and RBT were 69.7%, 87.7%, and 91.2%, respectively, with a combined sensitivity of 92.6%. ROC analysis identified CRP as a highly sensitive and specific biomarker (cutoff: 4.07 mg/mL; sensitivity: 84.2%, specificity: 72.2%; Z = 5.568, p < 0.001). All patients were treated with doxycycline and rifampicin for 3 months, with 34% requiring surgical intervention. The prognosis was satisfactory in all cases.ConclusionsBrucellosis arthropathy, often chronic and predominantly affecting the knee and hip joints, presents with septic arthritis, joint effusion, and bone destruction on imaging. Diagnosis can be effectively achieved through aerobic joint fluid-blood bottle culture, SAT, and RBT. Early diagnosis and combined medical-surgical management yield favorable outcomes.